Evaluation of nephrotoxicity and ototoxicity following amikacin administration once daily or every 48 hours in neonates. Issue 43 (28th October 2022) - Endo, Aiju; Hanawa, Kazumi; Nemoto, Atsushi; Ishikawa, Takahiro; Kazama, Shizuka; Kagami, Yu; Maebayashi, Yuki; Katsumata, Nobuyuki; Naito, Atsushi; Kobayashi, Yoshifumi; Kawano, Yayoi; Hanawa, Takehisa
Abstract : The purpose of this study was to evaluate the effects of once daily (OD) or every 48 hours (every-48-h) administration of amikacin (AMK) on renal function and ototoxicity in neonates. We investigated the frequency of nephrotoxicity and ototoxicity in neonates who received AMK OD or every-48-h from April 2015 to March 2021 and underwent dose evaluation by therapeutic drug monitoring (TDM). In addition, the relationships among birth weight, gestational age, AMK peak and trough values, total duration of AMK administration, and total AMK dose were examined separately for nephrotoxicity and ototoxicity. AMK was administered OD in 38 patients and every-48-h in 62 patients. Nephrotoxicity was observed in 8 patients on OD versus 36 patients on every-48-h administration ( P < .001), and ototoxicity was observed in 2 patients on OD versus 12 patients on every-48-h administration ( P = .192). For nephrotoxicity, only the trough value was relevant ( P = .007). In terms of ototoxicity, there were no influencing factors. The risk of nephrotoxicity was higher with every-48-h AMK administration than with OD AMK administration, with nephrotoxicity depending on the trough value. However, compared with OD, the every-48-h group had lower body weight and possibly poorer original renal function. In addition, ototoxicity did not differ by administration method. Based on these results, every-48-h administration of AMK can be used as safely as OD by performing TDM and preventing high concentrations.